Problem Based Learning (PBL) Learning Model At Sman 1 Mukomuko - Prasetyo, Mohammad; Zufiyardi, Zufiyardi; Sazili, Sazili (Universitas Dehasen Bengkulu, 2025)
This study aims to examine the implementation of the Problem Based Learning (PBL) model in improving student learning outcomes in Economics subjects at class X.E9 of SMAN 1 Mukomuko. The research employed a Classroom Action Research (CAR) method conducted in three cycles, each consisting of planning, action, observation, and reflection stages. The research subjects were 32 students, consisting of 11 males and 21 females. Data were collected through observation of student learning activities and learning outcome tests (pre-test and post-test). The results showed that the application of the PBL model effectively enhanced students' learning activity and outcomes. Student activity increased from 79% (cycle I) to 90% (cycle II), and reached 100% (cycle III). The average learning outcomes improved from 77.97 (cycle I) to 82.97 (cycle II), and further to 90.16 ( cycle III). It can be concluded that the Problem Based Learning model is effective in enhancing students' learning outcomes at SMAN 1 Mukomuko.